2021
DOI: 10.35314/inovbiz.v9i1.1801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transformational Leadership, Job Satisfaction, and Organizational Commitments on Organizational Citizenship Behavior

Abstract: The purpose of this study was to determine and examine the effect of transformational leadership, organizational commitment and job satisfaction on organizational citizenship behavior in high schools in Banten Province. The sample in this study was taken from 220 managers of supply chain management implemented company  respondents. Sampling in this study using the Simple Random Sampling technique. The analysis technique used is multiple regression analysis. The results of the analysis and testing show that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 4 publications
5
55
2
8
Order By: Relevance
“…This result is not in line with research by Noruzy et al ( 2013 ) and Nguyen and Luu ( 2019 ) stated that work motivation had no significant effect on performance. Organizational culture had a significant effect on Millennial generation employee motivation, this result is in line with research by Prayuda ( 2019 ) and Purwanto et al ( 2021 ) stated that work motivation has a significant effect on performance. This result is not in line with research by Singgih et al ( 2020 ) and Sunarsi et al ( 2021 ) state that work motivation has no significant effect on performance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result is not in line with research by Noruzy et al ( 2013 ) and Nguyen and Luu ( 2019 ) stated that work motivation had no significant effect on performance. Organizational culture had a significant effect on Millennial generation employee motivation, this result is in line with research by Prayuda ( 2019 ) and Purwanto et al ( 2021 ) stated that work motivation has a significant effect on performance. This result is not in line with research by Singgih et al ( 2020 ) and Sunarsi et al ( 2021 ) state that work motivation has no significant effect on performance.…”
Section: Discussionsupporting
confidence: 89%
“…Transformational leadership gives confidence to employees that they can achieve results, this is one form of motivation received by employees. According to the results of the questionnaire filled in by the respondents, according to Prayuda ( 2019 ), Singgih et al ( 2020 ), Suprapti et al ( 2020 ), Purwanto et al ( 2021 ), and Sunarsi et al ( 2021 ), employees feel effectively facilitated to carry out learning that occurs in the organization. This is because transformational leaders are able to mobilize existing resources to complement, strengthen, and improve the quality of everyone in the organization to be involved in achieving goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the perceived organizational support modifies the correlation between participation in work and job satisfaction so that at a low level of participation in work, the feeling of support by the organization makes a difference in job satisfaction. Purwanto et al (2021) figured out the effect of transformational leadership, organizational commitment, and job satisfaction on citizenship behavior in secondary schools in Banten County. The results of the study showed that transformational leadership has a positive and significant effect on organizational citizenship behavior, job satisfaction has a positive and significant effect on organizational citizenship behavior, and organizational commitment has a positive and significant effect on organizational citizenship behavior.…”
Section: Almentioning
confidence: 99%
“…Apart from the leadership and OCB factors that are closely related to employee performance, employee satisfaction is also very influential on their performance at work (Nugroho et al, 2020a ). Research results from Purwanto et al ( 2021 ) and Ridlwan et al ( 2021 ) show that leadership style affects performance through job satisfaction. This means that if the leadership style is good, then job satisfaction and performance will increase/improve.…”
Section: Introductionmentioning
confidence: 99%